2018
DOI: 10.1016/j.applthermaleng.2018.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of critical heat flux using spherical porous bodies in saturated pool boiling of nanofluid

Abstract: Quenching of a stainless-steel rod with a porous ceramic structure, i.e. honeycomb porous plate (HPP), attached to its lower surface was investigated in distilled water under saturated conditions at atmospheric pressure. The experiments were performed on bare surface (BS) and on a TiO2 nanoparticle-deposited surface (NPDS). When the HPP was attached, the quenching rate increased significantly on both tested surfaces. The quench time for the NPDS with the HPP it was 28-times shorter than that for the bare stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…As compared to untreated flat Cu surface, the two-tier structures resulted in maximum CHF enhancement of 119.3%, followed by microgrooves by 110.5% and CuNWs by 68.6%. Mori et al [159] proposed coating of hybrid porous cellulose beads and TiO2 nanofluid for the enhanced NBHT performance on a curved surface. The study reported 2 times enhancement of CHF.…”
Section: Micro-scale Coatingsmentioning
confidence: 99%
“…As compared to untreated flat Cu surface, the two-tier structures resulted in maximum CHF enhancement of 119.3%, followed by microgrooves by 110.5% and CuNWs by 68.6%. Mori et al [159] proposed coating of hybrid porous cellulose beads and TiO2 nanofluid for the enhanced NBHT performance on a curved surface. The study reported 2 times enhancement of CHF.…”
Section: Micro-scale Coatingsmentioning
confidence: 99%
“…The results indicated a stable enhancement in CHF during the boiling period. Additionally, Mori et al [ 24 ] suggested adding a plate of honeycomb on the heating area while using TiO 2 NF in a saturated PB, and a significant enhancement of CHF was observed by maximum implementation of the new technique with NFs. In addition, TiO 2 NF has been investigated in PB by Hadži’ et al [ 25 ] and an improvement in CHT of NF at 0.1 wt.% of NPs compared to DW was reported.…”
Section: Introductionmentioning
confidence: 99%
“…The CHF represents a state which at fewer heat fluxes, the system is at the stable and safe working conditions. 4,5 A lot of research has been done on the pool boiling, which generally leads to two types of hot surface and hot wire experiments. 6,7 Also, many researchers have presented correlations for estimating CHF of pool boiling.…”
Section: Introductionmentioning
confidence: 99%